Perancangan Alat Bantu Memasukkan Gabah Ergonomis Ke Dalam Karung - Studi Kasus Di Penggilingan Padi Pak Santo - Antonius Hari Pratama; Heri Setiawan (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2020)
Pak Santo's rice mill is a rice mill located in the village of Tegal Arum. The factory serves the drying process until the rice mill. In carrying out the work process, factory workers use traditional methods, ranging from drying to packaging. Productivity in the process of packaging unhusked rice placed in a sack still requires more than 60 second/sack in a sack containing 25 kg, so it is less efficient in working time. The use of old tools is considered to be less effective, comfortable, safety, healthy, and efficient. Workers’ body posture when packing rice activities is considered unergonomics to be unhealthy because it causes muscle fatigue in the left-right shoulder and back based on initial observations using the Nordic body map questionnaire. From this problem the researchers designed an ergonomic tool to insert rice into sack